Energy return of different shapes of track spikes - Bahamonde, R.; Streepey, J.; Goyke, L.; Myers, A.; Mikesky, A. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Different track spike designs (pin, pyramid, post, Christmas tree, and modified Christmas tree) are all touted as being advantageous for track and field performance, but these claims have not been tested and reported in peer-reviewed literature. The purpose of this study was to examine how track spike design impacted energy return on a Mondo track surface. Load-deformation curves of the spikes driven by a machine into the track surface were determined and the energy absorbed and the energy returned by each spike was calculated. On the Mondo track surface, the modified Christmas tree design generated significantly more energy return than the other spike designs while the pin spike absorbed (and therefore returned) significantly less energy than the other spike designs. This information could useful for athletes and coaches looking to enhance performance on a Mondo track.